Impact of Bariatric Surgery on Ghrelin and Obestatin Levels in Obesity or Type 2 Diabetes Mellitus Rat Model. (9th February 2014) - Zhou, Donglei; Jiang, Xun; Ding, Weixing; Zhang, Dingyu; Yang, Lei; Zhen, Chengzhu; Lu, Liesheng
Abstract : We aimed to evaluate the therapeutic efficacy on weight control by different bariatric surgeries and investigate the ghrelin and obestatin changes after these surgeries in obesity and nonobese type 2 diabetes mellitus (T2DM) rats. Obese rats were randomly assigned to receive sleeve gastrectomy (SG, n = 8 ), minigastric bypass (MGBP, n = 8 ), roux-en-Y gastric bypass (RYGBP, n = 8 ), and sham operation (SO, n = 4 ). Another 4 rats served as control. Besides, Goto-Kakisaki (GK) rats were also randomly divided into similar groups except for total gastrectomy (TG, n = 8 ) group. The results showed that in obese rats, weigh loss in RYGBP group was similar to that in MGBP group but larger than that in SG group. Ghrelin significantly increased in RYGB group, but obestatin increased in MGBP group. Ghrelin/obestatin ratio significantly decreased in SG group. In GK rats, weight loss was most obvious in TG group. Postoperatively, ghrelin was significantly increased in MGBP and RYGB groups but decreased in TG group. Obestatin also showed an increase in MGBP and RYGB groups. Ghrelin/obestatin in TG group decreased significantly. In conclusion, RYGB and MGBP may be more suitable for obese rats, but TG may be the best strategy for T2DM rats to control weight with different mechanisms.